Incidence of obesity and anemia in the diagnosis of breast cancer - Martínez Cordero, Erika; Fernández Carrasco, María del Pilar; Vera Becerra, Luz Elvia; Esparza Martínez, Carlos Alberto; Apolinar Jiménez, Evelia (Progress in Nutrition, 2022)
Obesity (Ob) and anemia are common pathologies associated with a poor prognosis during breast cancer (BC) treatment. However, there are not enough data on the presence of these pathologies at the time of diagnosis, resulting in a late medical-nutritional intervention, which entails a wide variety of complications that affect the quality of life and prognosis of patients. This study analyzed the presence of Ob and anemia retrospectively in 715 women who were diagnosed with BC. The mean value for the body mass index (BMI) was 29.12kg/m2 while the highest prevalence in the analysis by age groups was for overweight and Ob; age and BMI showed a positive correlation. 15.43% of the women presented anemia and only a negative correlation trend was observed between hemoglobin values ​​and BMI. The results showed that 7 out of 10 women are overweight and 1 in 6 is anemic, the highest prevalence of anemia was in the overweight group.